Implementasi Gerakan Literasi Sekolah pada Kegiatan Kokurikuler Di SMA Negeri 1 Ngantang - Sri Narindra Wahyu Widayat; Suyono Suyono; Gatut Susanto (Universitas Indraprasta PGRI, 2026)
This study aims to describe the implementation of the School Literacy Movement (GLS) in co-curricular activities at SMA Negeri 1 Ngantang. The research method used is descriptive qualitative. The data of this study is in the form of information about the application of GLS in three stages of literacy, namely habituation, development, and learning in co-curricular activities. In addition, it also describes the application of six aspects of basic literacy such as reading and writing, numeracy, science, financial, digital, and culture or citizenship in co-curricular activities. Data collection was carried out through observation, interviews, and document studies. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions from literacy and co-curricular program documents that include program lists, activity classifications, program documentation, and student work portfolios. The results of the study indicate that the three stages of literacy, namely habituation, development, and learning, as well as the six aspects of basic literacy have been well implemented through co-curricular activities. Habitual activities are carried out through reading and writing activities or listening to information from multimodal texts according to the co-curricular activity material. Development activities are carried out by processing reading results into meaningful works that increase the level of critical thinking and creativity. Learning activities integrate six basic literacies into co-curricular activities through interdisciplinary learning. Thus, by implementing literacy in co-curricular activities, both programs, literacy and co-curricular, can run effectively and strengthen each other.